2011
DOI: 10.1063/1.3549159
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ions produced by laser ablation of several metals at 193 nm

Abstract: Influence of excited state spatial distributions on plasma diagnostics: Atmospheric pressure laser-induced He-H2 plasma J. Appl. Phys. 112, 083302 (2012) Characterizing the energy distribution of laser-generated relativistic electrons in cone-wire targets Phys. Plasmas 19, 103108 (2012) Verification of the physical mechanism of THz generation by dual-color ultrashort laser pulses Appl. Phys. Lett. 101, 161104 (2012) ORION laser target diagnostics Rev. Sci. Instrum. 83, 10D732 (2012) Target normal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…Previous studies on the laser ablation of beryllium are sparse [22,23]. Aluminum however has been the subject of several ablation studies using time-of-flight [24][25][26] and charge collection measurements [22,[27][28][29]. In all of these studies, significant ion production was typically observed for laser fluences around 1-2 J cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the laser ablation of beryllium are sparse [22,23]. Aluminum however has been the subject of several ablation studies using time-of-flight [24][25][26] and charge collection measurements [22,[27][28][29]. In all of these studies, significant ion production was typically observed for laser fluences around 1-2 J cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…With a positive bias, electrons can reach the probe surface, giving rise to a negative current, the value depending on the bias voltage and the TOA. As has been observed before, the magnitude of the detected negative current signals greatly exceeds the positive current signals, due to the much lower electron mass [4][5][6][7]. With decreasing laser fluence, the amplitudes of the positive and negative current signals decrease, while their arrival times are delayed, indicating a decrease in the amount and expansion velocity of the laser ablation plume.…”
Section: Resultsmentioning
confidence: 76%
“…4 Langmuir probe analysis is most suitable when one ionic species is dominant, as is the case for ablation of an elemental metal target. 5 However, for many PLD applications compound targets with a complex chemical composition are used and different ionic species are present in the plasma, all of which contribute to the ion current signal in a Langmuir probe measurement. Mass spectroscopy may be used to distinguish different ion masses and charge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used different target materials (C, Al, Mo, W) for this study to get a better understanding of when and where interpenetration or stagnation happens at the colliding interface. 29 In laser produced plasmas, the physical and chemical properties 30,31 of the target are one of the governing factors determining the ion charge state, velocity, particle density, etc. Hence, depending upon the target material, the generated plume's ion emission features (velocity, flux) as well as plasma properties (temperature, density) will vary even at constant laser intensity.…”
Section: A Iccd Fast Imagingmentioning
confidence: 99%